Effects of treated wastewater irrigation on soil properties, nutrient uptakes, and crop yields of agronomic crops under different crop rotations - Saleh, Mohammad; Salehi, Mobin; Khanaki, Shayan; Ebrahimian, Hamed; Liaghat, Abdolmajid; Mousavi, Seyed Majid; Pashapour, Salar; Ashrafi, Ali (Agricultural water management, 2025)
The global agricultural sector, as the largest consumer of water, faces critical challenges related to freshwater scarcity and quality. Treated wastewater (TWW) irrigation presents a viable solution, prompting this study to examine its effects on soil and crops over a two-year experiment (2020–2021) in Hashtgerd and Mahdasht, Karaj, Iran, across different growing seasons. Wheat, barley, alfalfa, and maize were cultivated in two farms per region. Findings revealed significant impacts on electrical conductivity (EC), nutrient levels (nitrogen and phosphorus), and heavy metal dynamics, varying based on TWW quality and soil properties. Notably, soil EC increased by 1.08 and 1.38 dS/m in Hashtgerd farms, while Mahdasht saw rises of 3.36 and 3.20 dS/m, reflecting regional disparities in TWW composition. Nitrate concentrations in Mahdasht increased by up to 25 mg/kg compared to baseline levels, while lead accumulation remained below critical thresholds in both regions. These region-specific values reflect local variations in water quality and soil characteristics, contributing to a broader understanding of spatial differences in TWW irrigation outcomes. While TWW enriched the soil with nutrients like nitrogen and phosphorus, it also posed risks such as salinization, nitrate leaching, and heavy metal accumulation, especially in Mahdasht, where wastewater quality is lower. Crop productivity improved for maize and barley under TWW irrigation, but wheat and alfalfa showed inconsistent outcomes, including occasional yield declines and nutrient imbalances. Although heavy metals in crops remained mostly within safe limits, nickel and lead exhibited worrisome trends. These findings emphasize the dual role of TWW in improving soil fertility and crop productivity while presenting environmental and health challenges. [Display omitted] •TWW irrigation enhances soil nutrients but poses salinization and heavy metal risks.•Heavy metal levels stayed mostly safe, but nickel and lead need ongoing monitoring.•Maize and barley yields improved; wheat and alfalfa had mixed responses.•Regional differences in TWW quality influenced soil and crop responses.•Sustainable TWW management ensures agricultural benefits and reducing risks.